Increasing Vocabulary of Grade VII Students at SMPS Miftaahul Khairaat Palu through Crossword Puzzle Game - Iftitah, Arika Nurul; Said, Mawardin M.; Suriaman, Aminah (MANAZHIM, 2024)
The main obstacles encountered by students to communicate in English is the lack of their vocabulary, Therefore, there should be strategic efforts made by teachers to increase students’ vocabulary mastery, like using Crossword Puzzle Game. The objective of this research was to examine whether the application of crossword puzzle game can increase vocabulary of grade VII students at SMPS Miftaahul Khairaat Palu or not. This study utilized the Class Action Research design, implemented in a cyclical process encompassing planning, action, observation, and reflection. The research involved 17 seventh-grade students during the academic year 2023-2024.This research was conducted in two cycles; the first cycle consisted of four meetings and the second one consisted of two meetings. Thus, there were totally six meetings in two cycles (cycle 1 and cycle 2). In collecting the data, there were three types of instruments used in this research: tests, observation sheets, and field notes. The results of quantities data analysis indicate that the mean score of posttests in cycle 2, 81.05 is higher than that of posttest in cycle 1, 69.05, and that of pretest in cycle 1, 60.58, Thus, based on the comparison of the students’ vocabulary achievement in pretest and in posttest in cycle 1 and in cycle 2, it can be concluded that the use crossword puzzle game can increase vocabulary of the grade VII students. While the results of qualitative data indicate that the students’ vocabulary increases from cycle 1 to cycle 2.